STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA APARATUR BAGIAN ADMINISTRASI DAN UMUM SEKRETARIAT DPRD KABUPATEN NUNUKAN DALAM MENINGKATKAN EFEKTIVITAS KINERJA - Erwin Sam; Nurmadhani Fitri Suyuthi; Syamsuddin Bidol (Universitas Ichsan Sidenreng Rappang, 2026)
This research aims to analyze the human resource development strategy and the performance effectiveness of civil servants in that division. This research uses a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving five purposively selected informants: the DPRD Secretary, the Head of the Budget Facilitation and Supervision Division, the Head of the General Affairs Division, a Junior Policy Analyst, and an Administrative Staff member. Data were analyzed through data reduction, data display, and conclusion drawing, with validity ensured through triangulation. The results show that the development strategy combines formal training, such as technical guidance and policy socialization, with informal development through senior-junior mentoring, cross-sectional task assignment, and self-directed workplace learning, although technology mastery remains uneven. Performance effectiveness is reflected in improved work skills, work achievement, competitiveness, adaptability to regulatory and digital changes, and resilience under council-duty pressures, though still constrained by data coordination and limited technological facilities. A well-directed, sustainable development strategy is proven to contribute to the effectiveness of the DPRD Secretariat's administrative support.